STANDARD AND NON-STANDARD GRAMMAR: TOWARD A CORRECT UNDERSTANDING OF GRAMMAR FOR CLASSROOM TEACHERS - Todd Hull (PUPIL: International Journal of Teaching, Education and Learning, 2025)
A majority of the literature about grammar in the EFL classroom concerns what if any role the teaching of grammar has in foreign language teaching. This presentation, however, will address the validity of the grammar rules which are presented in classrooms around the world by differentiating between descriptive and prescriptive approaches to grammar. It will define grammar, outline what a grammar error is and who makes grammar errors. It will then discuss how many of the purported rules that underpin curricula around the world are not rules but instead confusions with and reactions against natural language change, confusion of common tendencies with grammar rules, and the conflation of grammar and style. It will then give some concrete examples of these. Then it will discuss the implications for learners of a misunderstanding of grammar. Finally, it will address some common questions about understanding grammar properly in the descriptive sense rather than from a prescriptive standpoint.